Complement in the Initiation and Evolution of Rheumatoid Arthritis - Holers, V. Michael; Banda, Nirmal K. (Frontiers in Immunology, 2018)
The complement system is a major component of the immune system and plays a central role in many protective immune processes, including circulating immune complex processing and clearance, recognition of foreign antigens, modulation of humoral and cellular immunity, removal of apoptotic and dead cells, and engagement of injury resolving and tissue regeneration processes. In stark contrast to these beneficial roles, however, inadequately controlled complement activation underlies the pathogenesis of human inflammatory and autoimmune diseases, including rheumatoid arthritis where the cartilage, bone and synovium are targeted. Recent studies of this disease have demonstrated that the autoimmune response evolves over time in an asymptomatic preclinical phase that is associated with mucosal inflammation. Notably, experimental models of this disease have demonstrated that each of the three major complement activation pathways plays an important role in recognition of injured joint tissue, although the lectin and amplification pathways exhibit particularly impactful roles in the initiation and amplification of damage. Herein we review the complement system and focus on its multi-factorial role in human patients with rheumatoid arthritis and experimental murine models. This understanding will be important to the successful integration of the emerging complement therapeutics pipeline into clinical care for patients with rheumatoid arthritis.